Rhinomaxillary mucormycosis masquerading as chronic osteomyelitis: A series of four rare cases with review of literature - Neeta Mohanty; Satya Ranjan Misra; Sujit Ranjan Sahoo; Sobhan Mishra; Vijeev Vasudevan; S Kailasam (Wolters Kluwer Medknow Publications, 2012)
In a dental hospital, patients reporting with exposed bone in the palate/maxilla with or without pus discharging sinuses are generally clinically diagnosed as osteomyelitis which can occur as a complication of odontogenic bacterial infections, traumatic injuries, herpes zoster infection, aspergillosis, mucormycosis or iatrogenic infections. We present a series of four cases, all of which were initially clinically diagnosed as osteomyelitis and later confirmed to be mucormycosis following histopathological examination. Although rare, the common form of this opportunistic fungal infection is seen in the rhinomaxillary region and in people with an underlying systemic disease like diabetes mellitus (DM). This case series of rhinomaxillary mucormycosis is being reported to increase awareness among dental surgeons to regard the occurrence of osteomyelitis in the maxilla occurring in a immunocompromised patient especially with poorly controlled DM, with suspicion of an aggressive, fulminant, fatal fungal infection so as to ensure an early diagnosis and prompt treatment thereby reducing the morbidity and mortality associated with this disease.